Contribution of fingertip light touch on postural stabilization of older adults - Barela, Ana Maria Forti; Caporicci, Sarah; Barela, José Angelo [UNESP] (Springer Nature, 2017)
In this study, we investigated the use of somatosensory information by older adults, with and without visual information. Ten older (67.3±4.8 years) and 10 younger adults (24.1±2.5 years) remained in the semi-tandem quiet stance on a force plate in the following experimental conditions, each 30 s long: no vision and no touch (NV-NT), no vision and touch (NV-T), vision and no touch (V-NT), and vision and touch (V-T). On the touch condition, participants touched lightly (<1 N) with their right index finger a rigid instrumented touch bar positioned laterally at their hip level. Mean amplitude of center of pressure (CoP) in the medial-lateral (ML) and anterior-posterior (AP) directions and mean absolute vertical and horizontal (AP and ML) forces applied on the touch bar were calculated. All participants swayed more in the NV-NT condition and presented no difference between V-NT and NV-T. In the NT conditions, older adults swayed more compared to younger adults, but no difference was observed between groups for the AP direction when touch was available. For the ML direction, there was no group difference when older adults used touch compared to younger adults with no touch. Older and younger adults were able to use light touch to reduce body sway; however, older adults presented higher variability to apply vertical and horizontal forces. Somatosensory information contributes to body sway as well as visual information, and older adults can benefit from that information, although they need slightly higher levels of applied forces during fingertip touch.
Keywords: Body sway; Center of pressure; Elderly; Force plate; Motor control; Postural control; Semi-tandem stance; Somatosensory information; Touch bar; Visual information